Enhancing quality of care for older adults: The age‐friendly health system (4Ms framework) and the role of general medicine physicians as system‐based complexologists - Masaya Higuchi; Takashi Watari; Kenya Ie (Journal of General and Family Medicine)
Abstract The aging population presents critical challenges to global healthcare systems, with Japan expected to have 35% of its population aged 65 or older by 2040. Older adults often experience multimorbidity, cognitive impairments, and physical frailties, increasing healthcare utilization and costs. Traditional medical approaches that focus on organ‐specific diagnoses are insufficient for addressing these multifaceted needs. The Age‐Friendly Health Systems (AFHS) framework, introduced in the U.S., offers a patient‐centered, value‐based approach to geriatric care, encompassing the "4Ms": Mentation, Mobility, Medication, and What Matters. These pillars prioritize cognitive health, physical function, appropriate medication use, and patient values. However, Japan has yet to implement this system widely. The integration of AFHS, with an additional focus on "Multicomplexity" (5Ms), aligns well with the core competencies of General and Family Medicine. This specialty is crucial in leading interdisciplinary efforts to enhance geriatric care, addressing fragmentation and variability in healthcare delivery. To successfully implement AFHS in Japan, general medicine physicians must be trained in managing complex conditions and coordinating care across specialties. This shift toward holistic, patientcentered care is essential for improving outcomes for older adults and reducing healthcare costs. Future research should focus on developing effective strategies for AFHS implementation and training healthcare teams for comprehensive care delivery.